Mastering the siege - De Bruyn, Dieter (Primerjalna književnost, 2009)
Master narratives of the relief of major cities can find their counterparts in particular individual accounts of the same events. Whereas the former tend to be "monologic" and are characterized by an "epic" plot, the latter may display features of "polyphony" and plotlessness. Works by Adamovich and Granin, and by Białoszewski, serve as illustrations.
Keywords: Bahtin, Mihail Mihajlovič, 1895-1975; literatura in ideologija; slovanske književnosti; svetovna vojna 1939-1945; Leningrad; Varšava; velika pripoved